ChemInform Abstract: 1‐(1‐Alkylsulfonic)‐3‐methylimidazolium Chloride Broensted Acidic Ionic Liquid Catalyzed Skraup Synthesis of Quinolines under Microwave Heating. Issue 46 (18th November 2014) - Amarasekara, Ananda S.; Hasan, Muhammad A.
Abstract The ionic liquid promoted Skraup synthesis of quinolines involving the in situ formation of acrolein by dehydration of glycerol under microwave conditions.